Linking organizational citizenship behavior and organizational trust towards reducing workplace deviance behavior in higher education - Ali Abbasi; Wan Khairuzzaman Wan Ismail (Cogent Social Sciences)
Deviance is complex unethical behavior that influences employees, groups, and organizations. When employees misbehave in the workplace, these behaviors can harm the system and prevent organizations from achieving their objectives. This paper examines the impact of trust and citizenship behavior on workplace deviance. It further investigates the mediator effect of organizational citizenship behavior between organizational trust and workplace deviance in tertiary education in Malaysia. The finding of this research from four hypotheses reveals the high impact of organizational trust on organizational citizenship behavior and the contrary effect of trust on deviant behavior in organizations. Our analysis found a significant impact of citizenship behavior as a mediation between organizational trust and workplace deviance, particularly in tertiary education. This study employs a quantitative method to test hypotheses through Partial Least Squares Structural Equation Modeling on 230 respondents from tertiary education in Malaysia. In theory, the current study’s findings have added to deviance as an indication of the unlike impacts of trust and citizenship behavior on workplace deviance. The discovery of the present investigation advocate reducing unethical behavior in higher education, thus improving employees’ efficiency and sustainability in tertiary education.